The first language syntactic interference in english writings of first - year english majors at Bac Lieu University - Huỳnh, Thị Út (2018)
Chuyên ngành: Ngôn ngữ Anh; Mã số: 82.20.20.1; Ý kiến về việc sao chép tài liệu: đồng ý; Ý kiến về việc chép file: đồng ý; TM tài liệu tham khảo sau phần kết luận; Luận văn Thạc sĩ Ngôn ngữ Anh ĐH Thủ Dầu Một, 2018; Chapter 1: Introduction; Chapter 2 Liteature review; Chaspter 3 Reseach methods; Chapter 4 Data analysis and discussion; Chapter 5. Conclusions, Implication, Limitations and recommendations